2019
DOI: 10.1002/jpen.1736
|View full text |Cite
|
Sign up to set email alerts
|

Immunonutrition vs Standard Nutrition for Cancer Patients: A Systematic Review and Meta‐Analysis (Part 1)

Abstract: The aim of this study was to determine the efficacy of immunonutrition vs standard nutrition in cancer patients treated with surgery. Cochrane Central Register of Controlled Trials, EMBASE, MEDLINE, EBSCOhost, and Web of Science were searched. Sixty‐one randomized controlled trials were included. Immunonutrition was associated with a significantly reduced risk of postoperative infectious complications (risk ratio [RR] 0.71 [95% CI, 0.64–0.79]), including a reduced risk of wound infection (RR 0.72 [95% CI, 0.60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 81 publications
3
105
0
7
Order By: Relevance
“…There were differences in deep neutrophil infiltration before and after intervention in both groups, without any statistical significance. We did not observe any differences between the groups with respect to morbidity (immune group, 4 (28.5%); control group, 3 (25%); p = 0.9095), length of hospital stay (immune group, 5 [4][5][6][7][8][9][10][11][12][13][14][15]; control group, 5 [4][5][6][7][8][9] (median (IQR)); p = 0.8402) There was no mortality and only one readmission in the control group.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…There were differences in deep neutrophil infiltration before and after intervention in both groups, without any statistical significance. We did not observe any differences between the groups with respect to morbidity (immune group, 4 (28.5%); control group, 3 (25%); p = 0.9095), length of hospital stay (immune group, 5 [4][5][6][7][8][9][10][11][12][13][14][15]; control group, 5 [4][5][6][7][8][9] (median (IQR)); p = 0.8402) There was no mortality and only one readmission in the control group.…”
Section: Resultsmentioning
confidence: 82%
“…While the use of nutritional support to prevent or treat malnutrition in the preoperative period does not raise wider concerns, the use of immunonutrition (nutritional support containing components that interfere with the immune system: arginine, glutamine, omega-3 fatty acids, nucleotides, and zinc) is not widely accepted. The positive impact of immunonutrition compared with standard nutritional support in the reduction of postoperative infectious complications and other surgical outcomes has been reported [ 5 , 6 ]. However, this only refers to short-term clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Immunonutrition has been investigated for decades, including arginine, glutamine, cysteine, n-3 fatty acids, nucleotides vitamins and trace elements [99]. However, according to the latest systematic review and metaanalysis [100], immunonutrition alone didn't reduce allcause mortality of cancer patients although reduces postoperative infection complications. In 1998, Vanderhoof conjectured the immunomodulatory effects of carbohydrates, which had little attention and few literature at that time [101].…”
Section: Dietary Immunomodulatorymentioning
confidence: 99%
“…This strategy is often used in critical illnesses (Calder, 2003). For example, a meta‐analysis of 61 randomized controlled trials on immunonutrition in cancer patients has shown that immunonutrition was associated with reduced risk of post‐operative infectious complications, including reduced risk for respiratory tract infection (Yu et al, 2019), compared with standard nutrition. In the study on immunonutrition in COVID‐19, patients with confirmed SARS‐Cov‐2 infection, who do not require intensive care unit admission, will receive oral nutrition supplement (ONS) enriched in eicosapentaenoic acid (EPA), γ‐linolenic acid (GLA), vitamin A, vitamin C, vitamin E, selenium and 5.7‐mg zinc (Oxepa, Abbott Nutrition, Abbott Laboratories) or isocaloric–isonitrogenous product (prepared by the same manufacturer).…”
Section: Clinical Trials On Covid‐19 Related To Zincmentioning
confidence: 99%